Collisional and Radiative Energy Loss in QED and QCD Plasmas - Javad Sheibani; Abolfazl Mirjalili; Kurosh Javidan; Reza Gharaei; Shahin Atashbar Tehrani (Iranian Journal of Astronomy and Astrophysics)
Evaluating the energy loss of an electrically (color) charged particle crossing a high-temperature QED (QCD) plasma at its thermal equilibrium is studied. The average energy loss depends on the particle characteristics, plasma parameters, and QED (QCD) coupling constant alpha (alpha s). All processes through which the energy of a particle changes can be categorized into two main mechanisms: elastic collisions and radiation through bremsstrahlung. We have introduced the final results of collisional and radiation energy loss for an electrically charged particle in a QED plasma, as well as a quark in a QCD plasma. The suppression due to radiation is presented using the Landau-Pomeranchuk-Migdal effect. Time evolution of particle distribution functions has been evaluated numerically through the Fokker-Planck equation. We have calculated the drag and diffusion coefficients using the collisional and radiation energy loss definitions. outcomes of different presented relations are different. We have compared differences and similarities in evolution of distribution functions.